Evaluation of Microorganism Profile and Antimicrobial Resistance Rates of Clinical Specimens Sent From Patients in Burn Units: A Five-year Tertiary Center Experience - Merve Gürler; Merve Akın; Mehmet Sefa Çamöz; Nilay Çöplü; Bedia Dinç (Journal of Global Antimicrobial Resistance)
AIM: This study aimed to evaluate the distribution of microorganisms isolated from all clinical samples of patients hospitalized in Burn Units (BU)(Burn Treatment Center and Burn Intensive Care Unit) and to evaluate antimicrobial resistance surveillance. BACKGROUND: In patients hospitalized in BU, resistant microorganisms are frequently detected due to long hospitalization periods, invasive procedures, and broad-spectrum antibiotic usage. METHODS: All clinical specimens sent to our laboratory from patients in Ankara Bilkent City Hospital BU between January 2020 and June 2024 were retrospectively analyzed.Identification and antimicrobial susceptibility of the isolated strains were performed by MALDI-TOF and VITEK-MS (bioMérieux,France), respectively.Antibiotic susceptibility results were evaluated according to the EUCAST criteria. Results-CONCLUSION: The number of clinical samples and demographic characteristics of patients hospitalized in BU are given in Table-1. The most frequently sent sample type was the blood/catheter sample. The most frequently isolated Gram-negative bacteria were Pseudomonas aeruginosa and Acinetobacter spp. while Gram-positive bacteria were Staphylococcus aureus and Enterococcus faecalis and fungi were Candida spp. It is noteworthy that the rates of Candida spp increased after 2022 and that Acinetobacter spp was not detected in 2024 (Figure 1).Carbapenem resistance in P.aeruginosa reached 95% and colistin resistance reached 10%.While resistance to almost all antibiotics in Acinetobacter spp. has been at very high percentages in all years, the rapid increase in the percentage of amikacin resistance is remarkable.Vancomycin resistance was not detected in E.faecalis isolates. However, the percentage of levofloxacin resistance has increased in these isolates in recent years.Methicillin resistance among S.aureus isolates reached 100% (Figure 2-5).